Manajemen Sumber Daya Manusia (SDM) Ritel dalam Meningkatkan Kinerja Perusahaan - Mubarak, Mumuh Mulyana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
Retailing is one of the worldâs largest industries. Behind the success of Retail Business, the Human Resources plays more positions in retail. The Corporate Performance was build by Human Resources. This Research explains of the questions to (1) Carier Positions in Retail Business (2) Jobs and Functions of Human Resources in Retail Business (3) The Resistances in Services Processes and Its Solutions. This Research used the Exploratorist Research to give knowledge and explanations about the themes. Keywords: Retail Business; Human Resources.